THE DEVELOPMENT OF FRACTION TEXTBOOK WITH THE ETHNOMATHEMATICS APPROACH FOR THIRD GRADE STUDENT OF MADRASAH IBTIDAIYAH - Putri, Linda Indiyarti; Nurwidiyanto, Nurwidiyanto; Rohmah, Alfiana (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2020)
The development of a fraction textbook with an Ethnomathematics approach for the third-grade student of Madrasah Ibtidaiyah (MI) has an urgency to be implemented in fulfilling the alternative needs for learning mathematics textually and realistically. This study aims to determine the effectiveness of fraction material textbooks with an ethnomathematics approach in Madrasah Ibtidaiyah. The population of the study was the third-grade students of MI Roudlotul Huda of Sekaran Gunungpati. The development model is carried out using the concept of development research according to Borg and Gall's 4D model. The sample of this study is using simple random sampling. Product trials were carried out in two class groups, namely IIIA as the experimental class and III B as the control class. The method of obtaining data used questionnaires, tests, and documentation. Then, the early step analysis of the data used the homogeneity and normality test. Furthermore, the data were analyzed using independent samples t-test and paired samples t-test. The product validation analysis results based on the material aspects state that the fraction textbooks with an ethnomathematics approach are suitable to use with a percentage of 75.8% and 75.8% from the material aspect. Meanwhile, response to textbook products in the attractive category obtained a percentage of 89%.